1981
DOI: 10.1172/jci110104
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctions of Pokeweed Mitogen-stimulated T and B Lymphocyte Responses Induced by Gammaglobulin Therapy

Abstract: A B S T R A C T Lymphocytes obtained from nonim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(19 citation statements)
references
References 46 publications
1
17
1
Order By: Relevance
“…It is, however, unlikely to be secondary to chronic infections since it was found in patient 3 at birth and in patient 8 who is in good health. Ecto-5'-NT deficiency cannot be a consequence of immunoglobulin replacement therapy (as has been suggested for decreased PWM responses in nonimmunodeficient children treated with gammaglobulin [47]), since is was detected in two of our patients before the initiation of treatment. Although ecto-5'-NT activity is a marker for T lymphocyte differentiation (22,23,48), with thymocytes having virtually absent activity, it is unlikely that low numbers of T cells with ecto-5'-NT activity in CAG and CVI patients can be explained merely by a block in T cell maturation.…”
Section: Resultsmentioning
confidence: 51%
“…It is, however, unlikely to be secondary to chronic infections since it was found in patient 3 at birth and in patient 8 who is in good health. Ecto-5'-NT deficiency cannot be a consequence of immunoglobulin replacement therapy (as has been suggested for decreased PWM responses in nonimmunodeficient children treated with gammaglobulin [47]), since is was detected in two of our patients before the initiation of treatment. Although ecto-5'-NT activity is a marker for T lymphocyte differentiation (22,23,48), with thymocytes having virtually absent activity, it is unlikely that low numbers of T cells with ecto-5'-NT activity in CAG and CVI patients can be explained merely by a block in T cell maturation.…”
Section: Resultsmentioning
confidence: 51%
“…These observation may also indicate an inhibition of anti-idiotypic activity in vivo, as described in vitro [12]. IgG may block macrophage and B cell Fc receptors inhibiting the anti-idiotypic antibody synthesis from B lymphocytes [13]. IgA and IgM remained unchanged for the whole period of treatment.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…One possible explanation is that the ability to produce immunoglobulins may be perturbed by IVIG. Durandy et al [23] have indicated that lymphocytes obtained from nonimmunodeficent children treated with intramuscular immunoglobulin have a reduced capacity to proliferate and mature into IgG-and IgM-secreting plasma cells in vitro after stimulation with pokeweed mitogen. In fact, IVIG therapy suppresses polyclonal B cell activation observed in the acute phase of KD [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, IVIG therapy suppresses polyclonal B cell activation observed in the acute phase of KD [24,25]. An alternative explanation is derived from the cellular immune perturbation caused by KD [23][24][25]. Microbial SAgs bypass normal antigen presentation by binding to class II major histocompatibility complex molecules on antigen-presenting cells and to TCR Vβ elements on T cells, and trigger T cell activation through this interaction [18,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%